Proses Komunikasi dan Partisipasi dalam Pembangunan Masyarakat Desa - Wahyuni, Sri (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
The Subject of this study are (1) analyze rural community participation in the Raksa Desa Program, to indicate the specific factor and determine the level of rural community participation, (2) to identify the accuracy/effectiveness of Raksa Desa Program in developing participation by communication process, and (3) to find out the formula for increasing rural community participation in Raksa Desa program by effective communication. This study was conducted by the survey in three villages of Ciampea subdistrict, they are Cinangka, Bojong Jengkol, and Cibanteng villages. The technical sampling was determined by stratified random sampling with the level of activeness. The respondent was 74 person who had received a gift of Raksa Desa Program in the batch-1. The result shows that firstly, community in these three villages have low in education, experience, and income; secondly the government intervention is high; thirdly, the communication process is dominated by top-down model; fourthly, participation criteria that are chance, ability, and motivation are also still low; fifth, the rural community participation in Raksa Desa Program is low. The government intervention by top-down communication is not effective in increasing participation criteria (chance, ability, and motivation) of the rural community in Raksa Desa Program. So, the rural community participation in Raksa Desa Program is low, because this program does not match with community needs. The rural participation is Raksa Desa Program can be improved by interactive and convergent communication process.